2013
DOI: 10.5551/jat.18283
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Critical Limb Ischemia Requiring Endovascular Therapy: An Analysis of a Multicenter Database of Japanese Patients with Critical Limb Ischemia Undergoing Endovascular Therapy

Abstract: Aim:We investigated whether any seasonal variation is observed in the incidence, severity and prognosis of critical limb ischemia (CLI) requiring endovascular therapy. Methods: We analyzed a multicenter database of 1,568 consecutive CLI cases undergoing primary endovascular therapy for infrainguinal lesions between July 2004 and June 2011. The monthly incidence was assessed according to the cumulative number of cases in each month, using a simple moving average. The data were fitted to a nonlinear regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Since PAD shares overlapping risk factors and pathophysiology with CAD, we hypothesized that CLTI would show significant seasonal variation. Supporting this hypothesis, a small Japanese registry reported a peak incidence and treatment of CLTI during the winter months 17 and seasonal variations in amputations were observed in a New York State cohort 18 . Characterization of seasonal variation in CLTI hospitalization and outcomes may allow for targeted identification and treatment of vulnerable patients as well as to help identify modifiable environmental risk factors.…”
Section: Introductionmentioning
confidence: 90%
“…Since PAD shares overlapping risk factors and pathophysiology with CAD, we hypothesized that CLTI would show significant seasonal variation. Supporting this hypothesis, a small Japanese registry reported a peak incidence and treatment of CLTI during the winter months 17 and seasonal variations in amputations were observed in a New York State cohort 18 . Characterization of seasonal variation in CLTI hospitalization and outcomes may allow for targeted identification and treatment of vulnerable patients as well as to help identify modifiable environmental risk factors.…”
Section: Introductionmentioning
confidence: 90%
“…As does ACS (42) , CLTI has seasonal variations in incidence, severity, and prognosis. Our former study analyzing 1568 patients with CLTI undergoing EVT demonstrated that the number of patients were smallest from summer to autumn and largest from winter to spring (43) . The severity (assessed with the Rutherford classification) and risk for major amputation also presented significant seasonal variation, with the peak roughly in winter and the trough roughly in summer.…”
Section: Clinical Features Of Clti #4: Seasonalitymentioning
confidence: 98%
“…However, data were so far limited regarding lower extremity peripheral artery disease (PAD), another cardiovascular disease that has now become a global health problem 4 ) and attracted increasing clinical attention 5 8 ) . We previously reported the seasonal variation of critical limb ischemia (CLI) undergoing endovascular therapy (EVT) 9 ) , but it remained to be validated by nationwide databases. Furthermore, whether another major symptomatic manifestation of PAD, namely, intermittent claudication (IC), will also have seasonal variation is still unrevealed.…”
Section: Introductionmentioning
confidence: 99%